Live music, liquor and the city: an examination of the influence of liquor regulation on place-specific live music activity - Ballico, Christina (2016)
Live music plays a central role in the cultural life of cities. It provides an enticing entertainment option for the public, while culturally enhancing the spaces within which it operates. The ways through which live music activity is facilitated vary from locale to locale, being influenced by a range of cultural attitudes and regulatory factors, which in turn determine the ways in, and circumstances under, which such activity can and cannot occur. This paper examines the tensions at play between place-specific live music activity and regulation that pertains to this sector. It reports on research undertaken in Perth, Western Australia in relation to liquor regulation which primarily governs the spaces in which locally-focused live original music occurs. As this paper argues, despite a range of initiatives in place to lift the creative and cultural identity of the city, much of this has failed to engage with local live music. In turn, and due in part to regulation which does not, in-situ, address the varying needs of the sector, it is limited in its ability to be recognised as making a vital contribution to the creative and cultural identity of the city.